APAKAH MANAJEMEN LABA TERMASUK KECURANGAN ? : ANALISIS LITERATUR - Deddy Kurniawansyah (Universitas Airlangga, 2018)
Many maintain that earnings management is harmful. This literature study explains and describe the issue from the outside perspective of earnings management. This research method used qualitative with literature study. The results of this study are Earnings management is not a fraud. Fraud is an “act of criminal deception” or a “deceitful behavior which may be punished by law”. Earnings management is within legitimate constraints, implying that the deviation of reported earnings from underlying or economic earnings due to earnings management is legitimate or authorized by accounting standards and corporate laws. The results of this study contribute as add to the treasury of financial accounting literature, especially accounting theory. The results of this research have important implication for regulators and lawmakers. Regulators tend to regard earnings management as harmful and in the need of immediate remedial action.